2021
DOI: 10.2147/ccid.s300960
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Hyaluronidase-Mediated Degradation Among Seven Hyaluronic Acid Fillers in Hairless Mice

Abstract: Purpose Hyaluronic acid (HA) is the most common injectable dermal filler used for soft-tissue augmentation, and can be removed non-surgically by directly injecting hyaluronidase. In this study, the hyaluronidase-mediated degradation of different types of HA fillers implanted subcutaneously at the back of hairless mice having filler residence time of four days or three months were compared. Methods Two sites at the back of female hairless mice were subcutaneously implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The intravascular half-life of hyaluronidases is short, spanning only 2–3 min because of the presence of plasma glycoprotein inhibitors [ 70 ]. In tissues, hyaluronidases have a more prolonged activity, remaining active for 24–48 h; nevertheless, some murine studies have shown a complete drop in activity after 3–6 h [ 71 , 72 ]. For this reason, hyaluronidase re-dosing every 1–6 h has been recommended in cases of FIVO [ 73 ].…”
Section: Hyaluronan Biophysiology and Aesthetic Applicationsmentioning
confidence: 99%
“…The intravascular half-life of hyaluronidases is short, spanning only 2–3 min because of the presence of plasma glycoprotein inhibitors [ 70 ]. In tissues, hyaluronidases have a more prolonged activity, remaining active for 24–48 h; nevertheless, some murine studies have shown a complete drop in activity after 3–6 h [ 71 , 72 ]. For this reason, hyaluronidase re-dosing every 1–6 h has been recommended in cases of FIVO [ 73 ].…”
Section: Hyaluronan Biophysiology and Aesthetic Applicationsmentioning
confidence: 99%
“…The degradation kinetic of the hydrogel is another crucial parameter that must be evaluated, in order to understand its lifetime in the body after implantation (for example, in aesthetic medicine or tissue regeneration applications) but also to evaluate its reversibility upon minimally invasive injection of hyaluronidases. Even if one of the purposes of the crosslinking process is to increase the HA hydrogel’s resistance to endogenous hyaluronidases, the physicochemical features of the polymer must allow rapid degradation if inappropriate applications occur [ 35 ]. Therefore, understanding the susceptibility of this new material to hyaluronidase-mediated degradation is a valid way to complete its safety assessment and its chemical characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit chemically modified, HA fillers can be promptly degraded upon injection of highdose hyaluronidase, which represents a key advantage of HA over other injectable materials from a safety perspective, especially to manage serious adverse events such as vascular compromise. 9,10 Additionally, the degree of HA modification, and the crosslinking technology used, can both impact the rheological properties of the final product, allowing to fine tune its strength and malleability. 11 As a result, multiple filler formulations, rheologically adapted to specific treatment areas and patient needs, have emerged over the past two decades.…”
Section: Introductionmentioning
confidence: 99%